Evaluation of Precipitation Variability With an Entropy‐Based Approach - Filiz Barbaros; Türkay Baran (Journal of Flood Risk Management)
ABSTRACT Global climate change has significantly altered meteorological conditions, leading to substantial shifts in temperature and precipitation patterns. These changes have increased the frequency and intensity of extreme weather events, posing significant risks to ecosystems, agriculture, and human settlements. This study analyzed precipitation variability in the Eastern Black Sea Basin—one of Turkey's most precipitation‐prone regions—using an entropy‐based approach. Long‐term precipitation data (1975–2012) from 11 meteorological stations were evaluated to determine the rain pattern variability and the susceptibility to extreme events. The Intensity Disorder Index (IDI), derived from Intensity Entropy (IE), was used to quantify fluctuations in precipitation patterns. The results revealed that the regions in the western part of the basin, especially around Ünye and Ordu, showed the highest variability due to the increase in the number of extreme precipitation events and the associated increased flood risk. Seasonal assessments have shown that precipitation variability is increasing significantly in the summer months, with an increasing number of extreme events, highlighting the increasing impact of climate change on seasonal precipitation distribution. The entropy‐based index maps developed in this study provide valuable insights for regional flood risk assessments, disaster preparedness, and water resource management. These findings underscore the necessity of incorporating entropy‐based methodologies in climate resilience strategies, aiding decision‐makers in mitigating the effects of climate change on hydrological systems.